PKM Penggunaan Metode Dalcroze dalam Pembelajaran Ritme di Sekolah Dasar Kabupaten Kupang - Yohanis Devriezen Amasanan; Agustinus Bedaama; Stanislaus Sanga Tolan; Ruminah Ruminah; Kadek Paramitha Hariswari; Vincensius Sekundus Uskono; Yosef Liberius Bifel; Maria Petrus Olin (Universitas Nurul Jadid, 2023)
The millennial generation is a generation that is very close to technology. The freedom to access social media through various platforms such as YouTube, Instagram, WhatsApp and Facebook as entertainment is more important than the learning they get from social media. One simple problem that occurs in the field is their wealth of knowledge about various genres of music is unfortunately not matched by basic knowledge about music itself. One of the simplest is rhythm and tempo. Elementary school children in the RT.22 Matani area are often unable to sing according to the tempo or rhythm of the song they are playing. It is very simple but it becomes the basis for them to develop their interest and talent in music. On the other hand, the ability to hear and read rhythm and tempo must be trained to develop the ability to read block notation and numbers. The solution offered by the PKM team is to use the Dalcroze Method in practicing rhythm and tempo so that learning simple basic music theory becomes comfortable and fun, of course the expected results are maximized